Affective Learning in Digital Education—Case Studies of Social Networking Systems, Games for Learning, and Digital Fabrication - Näykki, Piia; Laru, Jari; Vuopala, Essi; Siklander, Pirkko; Järvelä, Sanna (Frontiers in Education, 2019)
Technological innovations, such as social networking systems, games for learning, and digital fabrication, are extending learning and interaction opportunities of people in educational and professional contexts. These technological transformations have the ability to deepen, enrich, and adaptively guide learning and interaction, but they also hold potential risks for neglecting people's affective learning processes – that is, learners’ emotional experiences and expressions in learning. We argue that technologies and their usage in particular should be designed with the goal of enhancing learning and interaction that acknowledges both fundamental aspects of learning: cognitive and affective. In our empirical research, we have explored the possibility of using various types of emerging digital tools as individual and group support for cognitively effortful and affectively meaningful learning. We present four case studies of experiments dealing with social networking systems, programming with computer games, and “makers culture” and digital fabrication as examples of digital education. All these experiments investigate novel ways of technological integration in learning by focusing on their affective potential. In the first study, a social networking system was used in a higher education context for providing a forum for online learning. The second study demonstrates a Minecraft experiment as game-based learning in primary school education. Finally, the third and the fourth case study showcases examples of “maker” contexts and digital fabrication in early education and in secondary school. It is concluded that digital systems and tools can provide multiple opportunities for affective learning in different contexts within different age groups. As a pedagogical implication, scaffolding in both cognitive and affective learning processes is necessary in order to make the learning experience with emerging digital tools meaningful and engaging.